1988
DOI: 10.1007/bf00581653
|View full text |Cite
|
Sign up to set email alerts
|

Ion permeation through single ACh-activated channels in denervated adult toad sartorius skeletal muscle fibres: effect of temperature

Abstract: The gigaohm seal technique was used to study the effects of temperature on ion permeation through acetylcholine-activated channels. This was done in cell-attached patches of the extrajunctional membrane of chronically-denervated, enzyme-treated cells from sartorius muscle of the toad Bufo marinus. The predominant extracellular cation in the pipette solution was Na+. Single channel current-voltage curves were measured at different temperatures and electrodiffusion and three-site-four-barrier rate theory models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
3
6
1
Order By: Relevance
“…Indeed, it has been reported that the conductance of muscle-type nAChRs increases with increasing temperature [36], [37], [38], [39]. As has been discussed previously in connection with the effects of temperature on functional properties of acetylcholine-gated chloride channels from the pond snail Lymnaea [25], alternative possibilities for the effects that we have observed include temperature-dependent changes in single-channel kinetics and/or changes in the affinity of agonist binding.…”
Section: Discussionsupporting
confidence: 62%
“…Indeed, it has been reported that the conductance of muscle-type nAChRs increases with increasing temperature [36], [37], [38], [39]. As has been discussed previously in connection with the effects of temperature on functional properties of acetylcholine-gated chloride channels from the pond snail Lymnaea [25], alternative possibilities for the effects that we have observed include temperature-dependent changes in single-channel kinetics and/or changes in the affinity of agonist binding.…”
Section: Discussionsupporting
confidence: 62%
“…S4A and B). The increase corresponds to a Q 10 of 1.6, consistent with the permeation rate increase expected for ion channel pores [50]. We used patch capacitance measurements (ΔCp) to monitor changes in the dome area and parameterized the mechanical relaxation kinetics at both temperatures by curve fitting (Fig.…”
Section: Resultssupporting
confidence: 59%
“…For instance, it seems possible, that temperature increase leads to a higher conductance but also to shorter opening times of ion channels which could compensate and, thus, result in a lack of net effect. Generally, ion channel conductivity, gating kinetics and open probability are affected by temperature (Romey et al 1980;Ffrench-Mullen et al 1988;Quartararo and Barry 1988;Krasilnikov and Sabirov 1989).…”
Section: Shapes Of Nerve Impulsesmentioning
confidence: 99%